Influence of different types of eye movement and visual information about the behavior and dynamic posture ortoestático in subjects from 15 to 16 years and with different driving practices - Cacho, F. (Journal of Physical Education (Maringá), 2008)
The purpose of thisworkis the study of oculomotricity effect and the visual information about the postural orthostatic dynamic behavior. The sample is formed by 64 (sixty four) individuals (32 handball players and 32 handball students) of both sexes, and between 15 and 16 years old. Posturegraphic variables frequency (axis x and y) and area were obtained through the measure platform of KISTLER STRANGHT in a rhythm of 32 points/sec by channel, during 20 seconds (640 points). The variables time of equilibrium (right, centre, left) and the number of dislocations (right, centre, left) were obtained by stability platform model 16125from Lafayette Instrument Company. In the control of ocular movement direction was used EYEMARK RECORDER - NAC SYSTEM. The results show that age, sex, practice level and kind of ocular movement have influence on postural behavior.